A Literature Review on Risk Factors for Pneumonia in Toddlers - Sapridha Pulungan, Nanda Sapridha Pulungan; Sulistyorini, Lilis; Azizah, R (Dian Nuswantoro Semarang, 2025)
Background: Pneumonia leading morbidity and mortality in <5 years old children, with high incidence rates in developing countries, so a deep understanding of its health determinants is crucial in prevention efforts. Factors such as nutritional status, immunization status, home ventilation conditions, occupancy density, and ambient temperature have been reported to contribute to the incidence of pneumonia, but findings between studies show variations that require a comprehensive synthesis study. Objective: analyze the main risk factors on pneumonia in toddlers through a systematic review of accredited studies. Method: literature review was used by selecting articles from Scopus Q1–Q5 and SINTA 1–SINTA 5 indexed journals obtained through keyword-based searches on Google Scholar and ScienceDirect. Result: of the study showed that poor nutritional status, incomplete immunization, inadequate ventilation, high occupancy density, and sub-ideal room temperature were consistently associated with an increase in pneumonia incidence in toddlers. Conclusion:, pneumonia is a multifactorial disease requires an evidence-based holistic prevention approach. Novelty: this study lies in the presentation of a comparative synthesis of various recent accredited sources, thus providing an integrative picture of the dominant risk factors relevant to public health interventions.